Lactoferrin mediates epithelial-mesenchymal transformation by regulating the PI3K/AKT/mTOR pathway to inhibit nasopharyngeal carcinoma metastasis: Lactoferrin inhibits NPC metastasis via PI3K/AKT/mTOR pathway - Xu, Min; Fan, Ye; Zou, Guoying; Yang, Qi; Xu, Fei (Cellular and Molecular Biology, 2024)
Nasopharyngeal carcinoma (NPC) is a common malignant tumor of the head and neck. Epithelial-mesenchymal transition (EMT) is a major player in regulating NPC transfer. There is increasing evidence that lactotransferrin (LTF) is an important regulator of EMT conversion. However, the potential role and mechanisms of LTF in regulating NPC cell EMT remain unclear. In this study, quantitative real-time PCR (qRT‒PCR) and Western blotting were applied to measure the expression of LTF in NPC cells. Subsequently, the influences of LTF on the proliferation, migration and invasion of NPC cells were verified by functional acquisition experiments. Finally, Western blotting was used to analyze the effects of EMT-related proteins and phosphoinositol 3-kinase (PI3K)/Akt/mammalian rapamycin target (mTOR) signaling pathways. The data of this study indicate that LTF was underexpressed in human NPC cells, and upregulation of LTF could restrain NPC cell proliferation, invasion, migration and EMT transformation. Moreover, the effects of LTF on NPC cell metastasis and EMT are partly determined by the PI3K/AKT/mTOR pathway. This study suggests that LTF is a potential biomarker of NPC and that LTF-mediated EMT progression plays a tumor-suppressive role in the progression of NPC metastasis.